2012
DOI: 10.1080/10665684.2012.715534
|View full text |Cite
|
Sign up to set email alerts
|

Service Learning as a Pedagogy of Whiteness

Abstract: In this article we employ whiteness as a conceptual framework to contextualize how faculty develop and implement, and consequently how students experience, service learning. A vignette that illustrates the pervasiveness of whiteness in service learning is followed by an analysis that details how whiteness frames the teaching and learning in this service learning experience. Through this example and analysis, we seek to increase instructors' capacity and confidence to interrupt the patterns and privileges of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(112 citation statements)
references
References 20 publications
(13 reference statements)
2
99
0
Order By: Relevance
“…Second, SL programs have been criticized for not specifically aligning programming with needs of underrepresented students. Currently, SL experiences tend to be largely designed by White faculty and serve White students, who are less likely to be lowincome and first-generation (Mitchell, Donahue, & Young-Law, 2012). Such programs may be structured with the assumption that the participating students will be unfamiliar with the community with which they will partner, and thus engage students in boundary-crossing experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Second, SL programs have been criticized for not specifically aligning programming with needs of underrepresented students. Currently, SL experiences tend to be largely designed by White faculty and serve White students, who are less likely to be lowincome and first-generation (Mitchell, Donahue, & Young-Law, 2012). Such programs may be structured with the assumption that the participating students will be unfamiliar with the community with which they will partner, and thus engage students in boundary-crossing experiences.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may reflect the narrative of "crossing borders" mentioned earlier, whereby ABs and other service-learning programs are framed in terms of going into communities of "others" to engage in service. The "othering" language often present in service-learning programs that other studies have discussed (e.g., Mitchell et al, 2012;Seider & Hillman, 2011;Seider et al, 2013) may lead to a dynamic where issues of race and diversity are discussed only in relation to the "other," not in relation to students themselves. Interestingly, the findings from this study may imply that this dynamic is not just the case for White students involved in service-learning but also for Students of Color volunteering in communities with which they do not directly identify.…”
Section: Discussionmentioning
confidence: 99%
“…Along these same lines, other studies have found that Students of Color experience stronger feelings of discomfort and alienation than White students during the classroom component of service-learning experiences (Coles, 1999;Green, 2001). Such negative reactions are due in part to White students and faculty using "othering" language when referring to community members and assuming privilege on the part of all students within the service-learning program, sometimes at odds with the actual experiences of Students of Color (Mitchell et al, 2012;Seider & Hillman, 2011;Seider et al, 2013). Moreover, Students of Color may hesitate to participate in discussions about race within the context of service-learning experiences because they are often the only or one of a few Students of Color in the group and do not want to speak for their entire racial group (Novick, Seider, & Huguley, 2011;Seider et al, 2013).…”
Section: The Role Of Race In Service-learningmentioning
confidence: 99%
“…Some researchers in this field have offered suggestions for improving both institutional and community outcomes that include closer partnerships with community organizations even to the point of collaborative construction of the curriculum which includes service learning and a strong institutional commitment to community engagement and trust building [15,16]. Taking it further, Mitchell et al [17] offer strategies for "challenging the pedagogy of whiteness in service learning" by being intentional through examination of our assumptions about our students, the communities, and the objectives of the activity. Similarly, framing the conversation about the service learning opportunity to focus not only on helping the community meet their needs, but also on what skills and resources the community brings to the table, helps to see the community as empowered on its own, and as an active contributor to the project, not simply a passive recipient.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, framing the conversation about the service learning opportunity to focus not only on helping the community meet their needs, but also on what skills and resources the community brings to the table, helps to see the community as empowered on its own, and as an active contributor to the project, not simply a passive recipient. Finally, Mitchell et al [17] propose the use of active, instructor-led discussions around race and racism and the role it plays in interactions between and among the faculty, students, and the community. Actively leading a discussion on race issues can help reduce the nonconstructive dialog that is likely to occur between students on the periphery.…”
Section: Introductionmentioning
confidence: 99%